English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Time ran short in class and the class couldn't get all the notes about this stuff so i gotta problem like this...

2x+y=1
{
10x-4y=2

how the heck do i do all this??
help please??
much appreciation!!!!!!

2007-01-09 15:10:48 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

2x+y=1

y=1-2x

10x-4(1-2x)=2

10x-4+8x=2

10x+8x=2+4

18x=6

x=1/3

y=1-2(1/3)

y=1-2/3

y=1/3

check:

2(1/3)+1/3=1

2007-01-09 15:24:49 · answer #1 · answered by Tiff 5 · 0 0

well there are 2 ways you can do it. one is to make one of the variables equal so you can eliminate it, or the other is to solve for a variable and use that in the other equation. here:

~making one variable equal so it cancels out:
2x+y=1
{
10x-4y=2
multiply the first sentence through by 4.
so you have:
8x+4y=4 (dont forget: multiply all by 4, not just the variables)
10x-4y=2 (notice how now you have 4y and -4y)
so add them and you get:
18x=6
so you get:
x=6/18 or 1/3
now substitute back in for x 1/3 to find y: 2x1/3+y=1
2/3+y=1
y=1/3.

other way: solving for a variable and substituting it in
so lets take the first equation:
soving for y:
subtract 2x from 1 side, so you get:
y=1-2x
so substitute that into the equation:
10x-4(1-2x)=2
10x-4+8x=2
so then you get, 18x-4=2
then by solving with simple algebra,
you get 18x=6
x=1/3
now substitute back in:
10x1/3-4y=2
3 1/3-4y=2
-4y=4/3
y=1/3.
voila! lol
hope that helps!!!

2007-01-09 23:26:41 · answer #2 · answered by ♥♫☺bee yourself☺♫♥ 3 · 0 0

I - (2x+y=1
II -(10x-4y=2

Equation I:
y = 1 - 2x
Substitution y
Equation II:
10x - 4(1-2x) = 2
10x - 4 +8x = 2
18x = 2 + 4
x = 6/18
x = 1/3
Substitution of x:
y = 1 - 2x
y = 1 - 2(1/3)
y = 1 - 2/3
y = 1/3
Solution: {x, y elements of R | x = y = 1/3}
<>

2007-01-10 00:40:57 · answer #3 · answered by aeiou 7 · 0 0

Substitution Method

2x + y = 1
10x - 4y = 2

2x + y = 1
y = -2x + 1

10x - 4(-2x + 1) = 2
10x + 8x - 4 = 2
18x = 6
x = (1/3)

y = -2(1/3) + 1 = (-2/3) + 1 = (-2 + 3)/3 = (1/3)

ANS : ((1/3),(1/3))

-----------------------------------------

Elimination Method

2x + y = 1
10x - 4y = 2

Multiply top by 4

8x + 4y = 4
10x - 4y = 2

18x = 6
x = (1/3)

2(1/3) + y = 1
(2/3) + y = 1
y = 1 - (2/3)
y = (3 - 2)/3
y = (1/3)

ANS : ((1/3),(1/3))

2007-01-10 00:44:59 · answer #4 · answered by Sherman81 6 · 0 0

1)pick an equation and sole for a letter:
y=-2x+1
2)substitute -2x+1 into the second equation replacing y:
10x-(-2x+1)=2
3)solve for remaining letter:
x=4
4)replace answer back int step 1 to solve for y:
y=-2(4)+1 y=-7
5)write answer in point form:
(4,-7)

2007-01-09 23:25:59 · answer #5 · answered by rose a 1 · 0 1

fedest.com, questions and answers